2003
DOI: 10.1016/s0008-6363(02)00661-2
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of calcineurin in mouse causes sudden cardiac death associated with decreased density of K+ channels

Abstract: Since the downregulation of I(tof) was observed with overexpression of calcineurin and was also reversed by the calcineurin inhibitor CsA, we conclude that downregulation of I(tof) is a consequence of calcineurin overexpression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 42 publications
3
52
0
Order By: Relevance
“…Reduced Kv current densities and action potential prolongation are consistent findings in experimental LVH models [3][4][5][6][7][8][9]11 and in failing human hearts. 10,29 The analyses completed here, however, revealed that cellular hypertrophy (increased C m ) is the main factor in determining reductions in I to,f and I K1 densities, because the mean amplitudes of these currents in TAC and sham LV cells were not significantly different.…”
Section: Marionneau Et Al Mechanisms Underlying K ؉ Current Remodelinsupporting
confidence: 80%
See 2 more Smart Citations
“…Reduced Kv current densities and action potential prolongation are consistent findings in experimental LVH models [3][4][5][6][7][8][9]11 and in failing human hearts. 10,29 The analyses completed here, however, revealed that cellular hypertrophy (increased C m ) is the main factor in determining reductions in I to,f and I K1 densities, because the mean amplitudes of these currents in TAC and sham LV cells were not significantly different.…”
Section: Marionneau Et Al Mechanisms Underlying K ؉ Current Remodelinsupporting
confidence: 80%
“…Several previous studies have described reductions in K ϩ current densities with LVH or heart failure. [5][6][7][8][9][10][11]29 Most of these studies reported 30% to 50% decreases in K ϩ current densities, with cell membrane capacitances increased by approximately the same percentage. Although not reported, it seems likely that K ϩ current amplitudes were also largely unaffected in these previous studies and that increased cell size was the primary determinant of the reductions in K ϩ current densities.…”
Section: Relationship To Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcineurin activates the local production of NO by iNOS in cardiac myocytes, which significantly contributes to sudden death, heart block, left ventricular dilation, and impaired systolic performance in this murine model of cardiac hypertrophy induced by the overexpression of calcineurin. heart block; sodium current; sudden death; inducible nitric oxide synthase; transgenic overexpression of calcineurin TRANSGENIC OVEREXPRESSION of constitutively active calcineurin (CN/Tg) in cardiac myocytes results in profound concentric hypertrophy followed by ventricular dilatation, interstitial fibrosis, heart failure, and eventually sudden cardiac death (13,26,32,33,40). The sudden deaths relate to ion channelopathies, which are downstream consequences of abnormalities of calcium homeostasis (17) and an inflammatory process (6, 10, 27, 36).…”
mentioning
confidence: 99%
“…TRANSGENIC OVEREXPRESSION of constitutively active calcineurin (CN/Tg) in cardiac myocytes results in profound concentric hypertrophy followed by ventricular dilatation, interstitial fibrosis, heart failure, and eventually sudden cardiac death (13,26,32,33,40). The sudden deaths relate to ion channelopathies, which are downstream consequences of abnormalities of calcium homeostasis (17) and an inflammatory process (6,10,27,36).…”
mentioning
confidence: 99%